Labour : A Heterodox Approach - Vercherand, Jean; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This work is a theoretical reconstruction of the labour and job market, which explores the fundamental implications for the theories of consumption and growth.
Keywords: Science